Covid-19 As A Non-Traditional Threat To Human Security - Nurhasanah, Siti; Napang, Marthen; Rohman, Syaiful (Journal of Strategic and Global Studies, 2020)
December 2019 marks a change in the perception of security itself because the enemy is invisible in the form of a virus that can endanger human survival. In this article, the author wants to discuss changes in the perception of "threat" in security from a "visible" threat to an "invisible" threat. Library research was used by the author in this article. The author uses three concepts as the development of security, namely traditional security concept, non-traditional security concept, and national security concept to analyze the case. The findings show that invisible threat in the form of virus or pandemic does not need military readiness as in traditional security. It rather needs a good healthcare system as part of the national resilience of a country in facing threat.